The phenomenon of NFT (non-fungible tokens) as an accounting entity - U. Yu. Blinova; N. K. Rozhkova; D. Yu. Rozhkova (Вестник университета)
The emergence of the digital economy and increased activity in cyberspace have led to the creation of new technologies and digital products such, as non-fungible tokens (NFT). The article presents the arguments that justify the need to study NFT as an object of legal relations and an object of accounting. A brief description of these items has been given; their types and market of circulation have been studied, and, also the current legal provisions, Russian accounting standards and international financial reporting standards have been analysed. To define NFT as an accounting object, the types of accounting objects enshrined in Federal Law No. 402-FZ “On Accounting” have been considered and the criteria for their attribution in relation to NFT have been analysed. The legal and accounting problems associated with the emergence of a new object have been highlighted and the ways for further research in the field of creating an accounting methodology for NFT as a specific and highly promising digital product have been defined.